Thomas Luckmann on the Relation Between Phenomenology and Sociology: A Constructive Critical Assessment - Gros, Alexis Emanuel (2021)
In the present paper, I intend to systematically revisit Thomas Luckmann’s account of the relation between phenomenology and sociology and to assess its strengths and weaknesses in terms of constructive criticism. In order to achieve this aim, I will proceed in three steps. First (1), I will reconstruct the Luckmannian approach by means of an exhaustive analysis of his programmatic texts. Second (2), I will identify its strengths and merits. And finally (3), I will discuss its shortcomings and try to correct them in two ways, namely, by bringing Luckmann into a dialogue with other sociological-theoretical and phenomenological accounts, and by counteracting some of his problematic claims with alternative insights contained in his own work.